PEMIKIRAN PADA BIDANG SUFI DAN TARIKAT DAN PENDIDIKAN ISLAM - Supriyono, Bangbang (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
Sufi and tarikat thought is one of the important aspects in the development of Islamic spirituality that has made a major contribution to religious and social life. Despite facing challenges from secularization, modernization, and globalization, Sufi and tarikat teachings remain relevant and develop according to the dynamics of the times. This research aims to examine the history of thought in the field of Sufism and tarikat and how both adapt in the context of the modern world. The method used in this research is a qualitative approach with the type of library research, which relies on collecting and analyzing related literature. The results show that the history of Sufi and tarikat development includes the great contribution of Sufi figures and the spread of tarikat in various regions. Key Sufi and tarikat ideas such as tazkiyah, maqamat, and ahwal form the main foundation of their spiritual practices. Moreover, in the modern era, Sufism and tarikat have adapted by using technology and inclusive approaches, remaining relevant despite the challenges of secularization and globalization.